The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1021/jp303085h
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Carbazole Derivatives as Wide-Energy-Gap Host Material for Blue Phosphorescent Organic Light-Emitting Diodes

Abstract: 2,7-Difluo-carbazole and 2,4,5,7-tetrafluoro-carbazole were synthesized as new building blocks of wide-energy-gap host material for phosphorescent organic light-emitting diodes (PHOLEDs). These fluorinated positions in the carbazole ring were determined on the basis of density functional theory calculation results. Spectroscopic analyses supported the hypothesis that poly(Nvinyl-2,7-difluoro-carbazole) (2,7-F-PVK) with the fluorinated pendant group possessed a wide energy gap, leading to the exciton energy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Due to the imbalanced charge transportation, PVK-based devices require high driving voltages to operate but also underperform with blue dopants [71,72]. As origin of this counter-performance, PVK forms lower energy triplet dimers that quenches dopant emission and drastically reduces device efficiencies [81][82][83][84][85][86][87][88]. While using iridium(III) [bis(4,6-difluorophenyl)pyridinato-N,C 2 ]picolinate (FIrpic) as the dopant, the maximum power efficiency (PE) only reaches 0.8 lm/W [62].…”
Section: Pvk a Best Seller As Polymeric Hostmentioning
confidence: 99%
“…Due to the imbalanced charge transportation, PVK-based devices require high driving voltages to operate but also underperform with blue dopants [71,72]. As origin of this counter-performance, PVK forms lower energy triplet dimers that quenches dopant emission and drastically reduces device efficiencies [81][82][83][84][85][86][87][88]. While using iridium(III) [bis(4,6-difluorophenyl)pyridinato-N,C 2 ]picolinate (FIrpic) as the dopant, the maximum power efficiency (PE) only reaches 0.8 lm/W [62].…”
Section: Pvk a Best Seller As Polymeric Hostmentioning
confidence: 99%
“…[5][6][7] In addition, recent studies have reported that the molecules with small ∆E ST , so-called thermally activated delayed fluorescent (TADF) molecules, can facilitate intersystem crossing at room temperature, and hence highly efficient electroluminescence can be achieved without the assistance of heavy metal atoms such as Ir or Pt. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The energy difference between singlet and triplet states is usually considered to be twice the exchange energy (K), i.e., 2K. [24][25][26] This holds true only if both singlet and triplet states are of exactly the same nature, and the relaxations of their wavefunctions are neglected.…”
Section: Introductionmentioning
confidence: 99%
“…7 This strategy has also been successfully applied to the design and synthesis of TADF molecules. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] It is well known that intermolecular interactions often exert a significant influence on the intrinsic optical properties of molecules. For example, some Pt-containing blue phosphors, which were reported to emit orange light when forming excimers, were employed for single-dopant white OLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, poly(N-vinylcarbazole) (PVK) has undoubtedly been one of the most common polymeric host for http wide bandgap emitters [35][36][37]. However, PVK clearly underperforms with blue triplet emitters [38][39][40][41][42][43]. As main figure of merit, PVK benefits from a high triplet energy level (3.0 eV) that is nearly identical to that of a single carbazole unit as a result of its non-conjugated character [44].…”
Section: Introductionmentioning
confidence: 99%